Novel reactive elastomer-metal oxide composite : effect of filler size and content on swelling and reinforcement - Han, Dingzhi (2014)
A novel elastomer-metal oxide composite that swells and stiffens upon hydration will be presented. Conventional water-swellable elastomers filled with hydrogels absorb water and swell upon hydration but their modulus decreases as a result of fluid water diluting the rubber matrix. Reduced stiffness compromise the reliability of swellable elastomers used in sealing applications. One major application of swellable elastomers is fluid containment seals for zonal isolation in the oilfield. For effective sealing, the contact pressure between the seal and the surrounding wall should be high while deformation should be limited when a differential pressure is applied. Both conditions can be achieved by means of swelling and stiffening of the seal; hence, the new reactive elastomer-metal oxide composite is developed such that after it is exposed to water, the composite swells and stiffens simultaneously. Composites filled with different amounts of oxide were studied and it was observed that swelling up to almost 100% with an increase in modulus of about 200% could be achieved for the best performing compound. Composites filled with different sizes of the metal oxide were also studied. The finest filler was found to impart the greatest modulus, both before and after hydration, to the composite although swelling was slightly reduced compared with the larger particles. Another advantage of the composite for sealing purposes is that the swelling is largely retained even after complete removal of the solvent; i.e., drying.